Geschichte der Sprachenpolitik Kameruns, oder: der lange Weg nationaler Sprachen aus der Verbannung - Djomo, Esaïe (Stellenbosch Papers in Linguistics Plus, 2012)
A major characteristic of Cameroon's language policy during the colonial era as well as during the firstfour decades of the postcolonial era, is discrimination against all indigenous Cameroonian languages.This began when German was introduced after the arrival of the first colonisers in 1844 and lasteduntil the end of the First World War, after which the policy was continued by the French (in easternCameroon) and the English colonial administrators (in western Cameroon). Even after Independencein 1960, this policy was perpetuated and defended, now by the Cameroonian government who fosteredso-called "Official Bilingualism", a policy securing the development of French and English aslanguages of education, and of administration and general public use in the entire country. The firstattempt to put an end to this aspect of colonial policy occurred in 1996. Since then, a lot has been doneto overcome and correct the policy of banishment of local languages, so that the Cameroonianlanguages are now being introduced into the educational system.Keywords: Schlüsselbegriffe: Kamerun, Sprachenpolitik, Nationalsprachen, SprachrehabilitationCameroon, language policy, national languages, language revitalisation